Carbon-based materials for catalytic wet peroxide oxidation - Ribeiro, Rui (2020)
Advanced oxidation processes (AOP) are regarded as a suitable technological alternative to meet the increasingly demanding quality criteria for sustainable and safe urban water cycles and complying with the use of treated wastewater as a reliable alternative of water source.